Toward a Maqāṣid-Oriented Hermeneutics: Reinterpreting Qur'anic Migration Ethics in the Contemporary Muslim Diaspora - Moh. Nor Ichwan (RaSAIL Media Group, Semarang, Indonesia, 2026)
Contemporary forced migration has generated new ethical and hermeneutical questions for Muslims living as minorities across diverse diasporic settings. This article examines how key Qur'anic migration verses—Q. al-Nisāʾ 4:97–100, al-Ḥajj 22:58–60, and al-ʿAnkabūt 29:56—have been interpreted across classical and modern exegetical traditions. Using a qualitative comparative-hermeneutical method, the study analyzes selected interpretations of al-Ṭabarī, Ibn Kathīr, Muḥammad ʿAbduh, Rashīd Riḍā, Fazlur Rahman, Yusuf al-Qaradawi, and Quraish Shihab. The analysis focuses on three issues: the historical-normative logic of classical tafsīr, the contextual expansion of modern readings, and the methodological tensions produced by both approaches. The article argues that classical exegesis preserves textual fidelity and historical specificity, yet often remains limited in addressing modern forms of displacement. By contrast, contemporary contextualist readings increase ethical relevance, but may insufficiently define the normative boundaries of interpretation. To address this tension, the article proposes a maqāṣid al-sharīʿah-oriented hermeneutic as a mediating framework. Such an approach enables migration verses to be read in relation to religious freedom, human dignity, protection of life, and civic belonging while remaining anchored in the moral objectives of revelation. The study contributes to Qur'anic hermeneutics, Islamic migration ethics, and contemporary Muslim diaspora studies.